Time Trends in Weekend Warriors and Other Leisure-Time Physical Activity Patterns in Brazilian Adults, 2009-2023 - De Moraes-Ferrari, G (HUMAN KINETICS PUBL INC, 2026)
Background: Distinct patterns of leisure-time physical activity (LTPA) have been associated with different health outcomes. Yet, time trends of different LTPA patterns remain insufficiently described. In this study, we examined time trends (2009-2023) in the prevalence of the weekend warrior and other LTPA patterns among Brazilian adults and described their sociodemographic, lifestyle, and cardiometabolic profiles. Methods: This time-series study included 643,196 Brazilian adult participants (>_18 y) from the Vigitel surveys between 2009 and 2023. Adults achieving physical activity guidelines (>_150 min/wk of moderate or >_75 min/wk of vigorous LTPA) were classified as weekend warriors (1-2 sessions/wk), intermediate actives (3-4 sessions/wk), or regularly actives (>_5 sessions/wk). Prais-Winsten regression models were performed to identify time trends of LTPA patterns, as well as lifestyle factors and cardiometabolic conditions across LTPA patterns. Results: Adults achieving physical activity guidelines increased from 30.3% in 2009 to 40.6% in 2023, with higher levels among men, younger adults, and those with >_12 years of education. The weekend warriors pattern declined from 5.9% to 3.1% particularly among men, whereas intermediate (11.3% to 17.4%), and regularly active (13.0% to 20.1%) patterns increased. Among weekend warriors, smoking and binge drinking remained elevated, obesity prevalence doubled, hypertension increased, and diabetes remained stable. Conclusion: Leisure-time physical activity increased between 2009 and 2023 in Brazil. Weekend warrior pattern decreased, whereas intermediate and regularly active patterns increased during this period. Weekend warriors showed worse trends in smoking, binge drinking, obesity, and hypertension.